Current Investment and Loan for Agriculture in Korea and Its Implications - 박준기 (한국농촌경제연구원, 2012)
This report described investment and loan plans for the agricultural sector following the changing circumstances of Korea’s agricultural policies, the direct payment programs, the agricultural crop insurance and the management risk control schemes, which are considered to be key support policies for stabilized farmers’ management. The future agricultural policies should be oriented in the direction of creating future demand for advanced agri-food, controlling management risk of large-scale farmers, and improving old and small-scale farmers’ welfare and the rural living environment. Examination was made for the direct payment programs, the agricultural crop insurance, and the scheme for supporting management recovery by the farmland bank as detailed support policies. It is necessary to clarify the direction of direct payment programs, about whether it would be the single payment scheme as in the EU or the individual direct payment scheme. The agricultural crop insurance is necessary to prepare for conversion to price insurance and income insurance in terms of farmers’ management risk control. The management recovery support system faces diversified management risks with the increasing number of large-scale farmers. It is necessary to develop support systems of diversified types that can effectively control farmers’ management risk.
Keywords: investment and loan; direct payment; crop insurance; management risk control; agricultural policy; investment and loan; direct payment; crop insurance; management risk control; agricultural policy